Kinetic and Related Determinants of Plasma Triglyceride Concentration in Abdominal Obesity. Issue 10 (October 2015) - Borén, Jan; Watts, Gerald F.; Adiels, Martin; Söderlund, Sanni; Chan, Dick C.; Hakkarainen, Antti; Lundbom, Nina; Matikainen, Niina; Kahri, Juhani; Vergès, Bruno; Barrett, P. Hugh R.; Taskinen, Marja-Riitta
<x xml:space="preserve">Abstract</x> Objectives— Patients with obesity and diabetes mellitus have increased risk of cardiovascular disease. A major cause is an atherogenic dyslipidemia related primarily to elevated plasma concentrations of triglyceride-rich lipoproteins. The aim of this study was to clarify determinants of plasma triglyceride concentration. We focused on factors that predict the kinetics of very-low density lipoprotein 1 (VLDL1) triglycerides. Approach and Results— A multicenter study using dual stable isotopes (deuterated leucine and glycerol) and multicompartmental modeling was performed to elucidate the kinetics of triglycerides and apoB in VLDL1 in 46 subjects with abdominal obesity and additional cardiometabolic risk factors. Results showed that plasma triglyceride concentrations were dependent on both the secretion rate (r=0.44, P<0.01; r=0.45, P<0.01) and fractional catabolism (r=0.49, P<0.001; r=0.55, P<0.001) of VLDL1-triglycerides and VLDL1-apoB. Liver fat mass was independently and directly associated with secretion rates of VLDL1-triglycerides (r=0.56, P<0.001) and VLDL1-apoB (r=0.53, P<0.001). Plasma apoC-III concentration was independently and inversely associated with the fractional catabolisms of VLDL1-triglycerides (r=0.48, P<0.001) and VLDL1-apoB (r=0.51, P<0.001). Conclusions— Plasma triglyceride concentrations in abdominal obesity are determined by the kinetics of VLDL1 subspecies, catabolism being mainly dependent on apoC-III concentration and secretion on liver fat content. Reduction in liver fat and targeting apoC-III may be an effective approach for correcting triglyceride metabolism atherogenic dyslipidemia in obesity.